Religious Freedom in the Workplace in the Case Law of the European Court of Human Rights - Bień, Alicja (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Freedom of religion is one of the fundamental fundamental rights. As a human right, it is guaranteed by international law, European law, as well as national laws. It is a right that presents many challenges, especially in the context of the conflict between individual freedom, equality, and between individual autonomy and the collective freedoms of religious groups. Of particular interest is the issue of its protection in the work environment. The main purpose of the article is to examine whether the jurisprudence of the European Court of Human Rights (ECtHR) effectively regulates the issue of religious freedom in the workplace, providing employees with adequate protection. An analysis of Article 9 of the European Convention on Human Rights establishing religious freedom and the relevant ECtHR case law is carried out.